Simulasi efisiensi motor listrik axial bldc dengan bahan soft magnetik variasi kompaksi dan perlakuan panas menggunakan perangkat lunak ansys maxwell - Rino Herwangga; Muh Nizam; Miftahul Anwar (Mekanika: Majalah Ilmiah Mekanika, 2018)
The research was conducted to determine the efficiency of electric motors with soft magnetic composite and laminate by used software Ansys Maxwell. Soft magnetic composite material which was given 4, 5, and 6 tons of compaction pressure from previous research performed to fill the input data on electric motor efficiency simulation. The used datas were hysterisis curve which are resulted of VSM (Vibrating Sample Magnetometer) testing. Ansys Maxwell Rmxprt was used to simulate efficiency of electric motor. The results of Ansys Maxwell Rmxprt simulation were a relation curve between the efficiency  and the rotation of the electric motor. The results simulation of efficiency electric motor using soft magnetic composite core furthermore compared to the efficiency value of electric motor using laminate core. The results showed that the efficiency value of electric motor with soft magnetic composite with compacting pressure 4, 5 and 6 tons was 89,94 %, 89,97 %, and 90,62 % respectively. Efficiency value of electric motor with core laminate material was 91,22 %. The simulation showed that the value of a compaction pressure given on soft magnetic composite material affect on the efficiency of electrical motor. As a conclusion of this research that the efficiency value of electric motor trend increase with the value of compacting pressure on the material.